How Empowering Is Citizen Science? Access, Credits, and Governance for the Crowd. Issue 2 (1st June 2019) - Chen, Shun-Ling
Abstract: Web-based crowdsourced citizen science is an efficient method for scientists to collect and process data. Although lay persons obtain the opportunities to participate in research and engage with scientists, these crowdsourced projects generally maintain the traditional hierarchy of academic science. Lay persons have little say in project or platform governance, and institutional tools to hold project investigators accountable are almost nonexistent. This article examines how existing institutional policies address the question of distribution in crowdsourced citizen science, as it may further affect lay participants' role in the institution of scientific knowledge production and their access to research resources. This article begins by comparing the norms developed by citizen-science institutions. It then discusses examples from Galaxy Zoo to see how the results of research projects are distributed, both in the form of access to research outcome and in authorship. The article also discusses the potential conflicts that arise when crowdsourced projects are organized by for-profit companies and why citizen-science platforms should develop institutional norms to avoid such conflicts.